Innovation on Education and Social Sciences Proceedings of the International Joint Conference on Arts and Humanities (IJCAH 2021) October 2, 2021, Surabaya, Indonesia - Maureen, Irena Yolanita; Imah, Elly Matul; Savira, Siti Ina; Anam, Syafi'ul; Mael, Masilva Reynox; Hartanti, Lina (Taylor & Francis, 2022)
After a year of a global Covid-19 pandemic, still, we have more questions than answers to the future of education and our social life. It is more important than ever to follow the developments closely in the coming period, pay attention to critical concerns such as inequality, as well as positive signs of transformation and innovation in all aspects of the world of teaching and learning. Expectations on what the future brings will have to be based on solid research rather than short-term perceptions. The proceedings of IJCAH 2021 are an interdisciplinary platform for teachers, researchers, practitioners, and academicians to discuss the latest research findings, concerns, and practical challenges encountered and solutions adopted in the fields of Arts and Humanities. The subject areas within the proceeding are education, language learning, arts, culture, social sciences.